Model Dakwah Networking: Analisis Dakwah IDIAL-MUI dalam Penutupan Lokalisasi Prostitusi di Jawa Timur - AS, Sunarto (Jurnal Komunikasi Islam, 2018)
This article seeks to discuss in depth the model of networking proselytising conducted by the Asociation of Preachers in Localization Area (IDIAL) and the Indonesian Ulema Council (MUI) of East Java in attempting to close down prostitution practices in East Java. Using a participatory approach, this study concluded that the IDIAL-MUI networking da'wah model used both structural and cultural approaches. The structural approach was carried out by building and strengthening power networks, namely bureaucracy, politics and the military in the process of closing the "localization". Whereas the cultural approach is carried out through building networks amongst the social, economic, community, and tertiary organization sectors by using da'wah bi al-hal. In addition, the da'wah bi al-lisan (verbal) also conducted within the cultural approach through preaching and creating majlis taklim.